Pengembangan Sarana Informasi dengan Video Profil di TK RA Hidayatullah Surakarta - Tri Vulandari, Retno; Wijayanto, Hendro; Febrianto, R Arie; Remawati, Dwi; Lestari, Zannuba Anugrah Indah; Putri Pertiwi, Ina; Restu Utami, Widya; Mujirahayu Meyliana, Nirma (Redtech Putra Benua, 2024)
The development of information in Kindergarten RA Hidayatullah to be known to the public, it is necessary to make a profile video in the form of audio visual as a means of promotion so that the community will be able to easily receive information from Kindergarten RA Hidayatullah. It is hoped that after the profile video is made, it can give a positive story and as a means of promoting RA Hidayatullah Kindergarten which is easily accepted by the wider community. The data collection methods carried out include observation, interviews, and literature studies. By means of direct observation or survey at RA Hidayatullah Kindergarten, complete and accurate data will be obtained. In addition, the observation method has the advantage of being able to know clearly about the environmental conditions of RA Hidayatullah Kindergarten. This interview method is a data collection method carried out by providing questions in accordance with the video that will be done to the teacher who is responsible for delivering information about RA Hidayatullah Kindergarten. The purpose of the interview is to obtain the right information from trusted sources, then collect data by asking questions related to the theme of the thematic practice work being carried out. Literature study, collection and information as well as knowledge obtained from books about the theory concerned. The creation of this profile video is expected to make it easier to promote RA Hidayatullah Kindergarten and can be known by the wider community.